TRADISI MULANG PEKELEM: DULU DAN SEKARANG - Karini, Ni Komang Sugita; Permana, Nyoman Aditya; Mahendra, I Made Dani; Divayana, Rey Su; Dewi, Ni Putu Sasmika (Institut Agama Hindu Negeri Gde Puda Mataram, 2024)
This research was conducted to find out what differences occur in the implementation of the mulang pekelem tradition. The mulang pekelem tradition is a tradition carried out by the Hindu community on Lombok Island, which is held on Mount Rinjani. For the people on Lombok Island, Mount Rinjani is a sacred place that is the palace of the gods. It is said that Mount Rinjani is guarded by a beautiful goddess named Dewi Anjani. Dewi Anjani is a powerful female figure who was originally a human, but later turned into a genie queen. The story of the origin of Dewi Anjani has many versions and is believed to exist by the people of the island of Lombok so that the people in Lombok greatly revere Mount Rinjani. As a form of respect for the goddess Anjani, the mulang pekelem tradition is held. This mulang pekelem tradition is believed to be a form of gratitude to God and respect for Mount Rinjani and as a tradition of request for rain during the dry season. The method used in this research is a qualitative method. The techniques and types of data collection used are observation and interviews with sources related to the mulang pekelem tradition such as the pemangku, the committee, and Hindus who participate in the mulang pekelem tradition. Based on the results of the research, the differences that occur in the mulang pekelem tradition lie in banten, participants, transportation, committees, equipment and equipment, costs, and regulations for climbing Mount Rinjani. The existing differences make the mulang pekelem tradition more organized and there are conveniences in its implementation compared to the past.